2021
DOI: 10.4103/aip.aip_125_20
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Induced Sexual Dysfunction

Abstract: Background: Antidepressant drugs are frequently associated with sexual dysfunction. Sexual side effects affect the patients' quality of life and in the long term and can lead to noncompliance and relapse. However, studies covering many antidepressants with different mechanisms of action are scarce. Aims: The aim of this study is to compare the rates of sexual dysfunction among patients taking escitalopram, desvenlafaxine, and mirtazapine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Of the 269 participants, 90 (36%) were current antidepressant users at the time of presentation with the most common antidepressant types being SSRI or SNRI, which have been documented to negatively influence sexual function specifically dryness and delayed or absent orgasm in women. 27 In our sample, we found that…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Of the 269 participants, 90 (36%) were current antidepressant users at the time of presentation with the most common antidepressant types being SSRI or SNRI, which have been documented to negatively influence sexual function specifically dryness and delayed or absent orgasm in women. 27 In our sample, we found that…”
Section: Discussionmentioning
confidence: 50%
“…The association between depression and sexual functioning is further complicated by the use of antidepressants. Of the 269 participants, 90 (36%) were current antidepressant users at the time of presentation with the most common antidepressant types being SSRI or SNRI, which have been documented to negatively influence sexual function specifically dryness and delayed or absent orgasm in women 27 . In our sample, we found that SSRI or a combination of two or more antidepressants were associated with the poorest FSFI scores.…”
Section: Discussionmentioning
confidence: 68%